The lived identity: analysis of the novel Blūdas by Julijonas Lindė Dobilas - Šmitienė, Giedrė (Literatūra, 2015)
The model of the exchangeable identity is widely spread out in the academic discourse as well as in the common thought. On the contrary this paper deals with the passive identity as the sameness that functions in the corporeality of senses or acts. The passive identity anchored in a flesh in question here is treated as a generator of the declared identity.The following considerations in the paper are based on the novel Blūdas by Julijonas Lindė-Dobilas. The considerations begin with the identity set from the outside; then they cross over to specific experiential fields in which the own incorporated identity is recognized and elucidated for self awareness. The novel Blūdas is interpreted as the text where the national self-consciousness unfolds.